Clonal Hematopoiesis and Cardiovascular Risk: Atherosclerosis, Thrombosis, and beyond - Izzi, Benedetta; Fuster, José J. (Hämostaseologie, 2024)
Acquired mutations that lead to clonal hematopoiesis have emerged as a new and potent risk factor for atherosclerotic cardiovascular disease and other cardiovascular conditions. Human sequencing studies and experiments in mouse models provide compelling evidence supporting that this condition, particularly when driven by specific mutated genes, contributes to the development of atherosclerosis by exacerbating inflammatory responses. The insights gained from these studies are paving the way for the development of new personalized preventive care strategies against cardiovascular disease. Furthermore, available evidence also suggests a potential relevance of these mutation in the context of thrombosis, an area requiring thorough investigation. In this review, we provide an overview of our current understanding of this emerging cardiovascular risk factor, focusing on its relationship to atherosclerosis and thrombosis.
Keywords: CHIP; atherosclerosis; thrombosis; inflammation; TET2